2023
DOI: 10.1111/exsy.13237
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting COVID‐19 cases using dynamic time warping and incremental machine learning methods

Abstract: The investment of time and resources for developing better strategies is key to dealing with future pandemics. In this work, we recreated the situation of COVID-19 across the year 2020, when the pandemic started spreading worldwide. We conducted experiments to predict the coronavirus cases for the 50 countries with the most cases during 2020. We compared the performance of state-of-the-art machine learning algorithms, such as long-short-term memory networks, against that of online incremental machine learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Previous work has been done on COVID-19 forecasting using both classical and machine learning methods. Miralles-Pechuán et al compared the performance of state-of-the-art machine learning algorithms, such as long-short-term memory networks, against that of online incremental machine learning algorithms to predict the coronavirus cases for the 50 countries with the most cases during 2020 27 . Kasilingam et al used exponential growth modelling studies to understand the spreading patterns of SARS-CoV-2 and identify countries that showed early signs of containment until March 26, 2020 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has been done on COVID-19 forecasting using both classical and machine learning methods. Miralles-Pechuán et al compared the performance of state-of-the-art machine learning algorithms, such as long-short-term memory networks, against that of online incremental machine learning algorithms to predict the coronavirus cases for the 50 countries with the most cases during 2020 27 . Kasilingam et al used exponential growth modelling studies to understand the spreading patterns of SARS-CoV-2 and identify countries that showed early signs of containment until March 26, 2020 28 .…”
Section: Discussionmentioning
confidence: 99%
“…These methods have shown promising performance in modeling and forecasting COVID-19 cases. [12][13][14] In other research, methods for forecasting COVID-19 cases and trends have included manual fitting, where initial model parameters are chosen based on historical data, and automated fitting, where parameters are chosen based on candidate case trajectory simulations. 15 Polynomial regression, ARIMA, deep learning techniques, such as recurrent neural network (RNN), and generalized space-time (GST) ARIMA models have been used for COVID-19 forecasting.…”
Section: Previous Studies On Covid-19 Forecastingmentioning
confidence: 99%
“…The authors claimed that the proposed model can significantly reduce the prediction errors as compared to the traditional epidemic models. Researchers have investigated many machine learning and deep learning models to train prediction algorithms on COVID-19 data [1], [21], [33], [36]. The research studies are able to provide effective directions to control and manage the spread of a pandemic like COVID-19.…”
Section: Related Workmentioning
confidence: 99%